Laparoscopy‐assisted transduodenal excision of superficial non‐ampullary duodenal epithelial tumors. Issue 3 (7th May 2015) - Abe, Nobutsugu; Takeuchi, Hirohisa; Hashimoto, Yoshikazu; Yoshimoto, Eri; Kojima, Youhei; Ohki, Atsuko; Nagao, Gen; Suzuki, Yutaka; Horiai, Shinichi; Mizuno, Hideaki; Masaki, Tadahiko; Mori, Toshiyuki; et al.
Abstract Introduction Transduodenal excision (transduodenal submucosal dissection) is an alternative to pancreaticoduodenectomy for the treatment of benign and low‐grade malignant tumors of the duodenum. However, laparoscopic transduodenal excision or laparoscopy‐assisted transduodenal excision (LATDE) of such tumors has been rarely reported. In this paper, we present the preliminary results of LATDE in patients with superficial non‐ampullary duodenal epithelial tumors. Methods Three patients with superficial non‐ampullary duodenal epithelial tumors (mucosal adenocarcinoma, n = 1; tubular adenoma, n = 2) underwent LATDE. LATDE consists of four major procedures: (i) laparoscopic wide Kocher maneuver (mobilization of the pancreaticoduodenum); (ii) extracorporeal approach to the fully mobilized duodenum through the upper median longitudinal incision (4 cm in length); (iii) tumor excision by submucosal dissection under direct vision through longitudinal duodenotomy (4 cm in length); and (iv) hand‐sewn closure of the mucosal defect and duodenotomy. Results LATDE was successfully carried out without any intraoperative or postoperative adverse events. The mean operating time and estimated blood loss were 155 min and 17 mL, respectively. Contrast roentgenography on postoperative day 4 showed neither duodenal deformity nor disturbance of gastroduodenal emptying in any of the patients. Conclusions LATDE could eliminate the possibility of peritoneal or port‐site seeding of tumor cells because the duodenotomy and tumor excision are performed extracorporeally. The meticulously hand‐sewn closures of the mucosal defect and duodenotomy can minimize the possibility of postoperative hemorrhage and/or anastomotic leakage. LATDE is a feasible, safe, and minimally invasive treatment for patients with superficial non‐ampullary duodenal epithelial tumors that have no risk of lymph node metastasis in the first and second portions of the duodenum.